Biological control of Pseudomonas avenae with epiphytic bacteria isolated from corn plants. I. Frequency distribution of bacterial population from corn whorls - Lopes, Carlos Alberto; Stall, Robert E. (Pesquisa Agropecuaria Brasileira, 2014)
Total populations of epiphytic bacteria and the populations of three groups of bacteria (fluorescent pseudomonads, Erwinia herbicola, and Flavobacterium spp.) were determined in the fluid collected in the whorls of sweet corn plants, susceptible and resistant to bacterial leaf blight and stalk rot. Total bacterial populations varied by a factor of less than 100 at each sampling date for each cultivar, whereas this factor was often above 104 for the three groups of bacteria. No qualitative or quantitative differences were observed on bacterial populations between the two genotypes. The bacterial populations in the whorls were lognormally distributed, as indicated by the normal probability plotting of residuals and by the Shapiro-Wilk test for normality. Bulked samples, obtained by mixing the first dilutions of individual samples, caused on overestimation of 1.71 62, indicating that bulk samples should not be used for quantitative surveys on bacterial populations in corn whorls